The DEWI High-Level Architecture: Wireless Sensor Networks in Industrial Applications - Samano-Robles, Ramiro (2022)
This paper presents the High-Level Architecture (HLA) of the research project DEWI (Dependable Embedded Wireless Infrastructure). The objective of this HLA is to serve as a reference for the development of industrial Wireless Sensor and Actuator Networks (WSANs) based on the concept of the DEWI Bubble. The DEWI Bubble is a concept that can be used to integrate legacy industrial sensor networks with a modern, interoperable, and flexible IoT (Internet-of-Things) infrastructure. The DEWI Bubble is defined as a high-level abstraction of an industrial WSAN with enhanced interoperability (via standardized interfaces), dependability, technology reusability, and cross-domain development. The DEWI Bubble aims to resolve the issue of how to improve commercial WSAN technology to match the dependability, interoperability and high criticality needs of industrial domains. This paper details the criteria used to design the HLA and the organization of the infrastructure internal and external to the DEWI Bubble. The description includes the different perspectives, models or views of the architecture: the entity model, the layered model, and the functional model (including an overview of interfaces). The HLA constitutes an extension of the ISO/IEC 29182 SNRA (Sensor Network Reference Architecture) towards the support of wireless industrial applications in different domains: aeronautics, automotive, railway and building. To improve interoperability with existing approaches, the DEWI HLA also reuses some features from other standardized technologies and architectures. The DEWI HLA and the concept of Bubble allow networks with different industrial sensor technologies to exchange information between them or with external clients via standard interfaces, thus providing a consolidated access to sensor information of different industrial domains. This is an important aspect for smart city applications, Big Data, Industry 4.0, and the Internet-of-Things (IoT). The paper includes a non-exhaustive review of the state of the art of the different interfaces, protocols and standards of this architecture. The HLA has also been proposed as the basis of the European project SCOTT (Secure Connected Trustable Things) for security and privacy in the IoT.